The Brazilian Rise and the Elusive South American Balance - Luis Leandro Schenoni (German Institute of Global and Area Studies (GIGA), 2015)
Within the last 50 years, the Brazilian share of South American power has increased from one-third to one-half of the overall material capabilities in the region. Such a significant change in the regional power structure cannot have gone unnoticed by Brazil's neighbors. The article addresses the main question related to South American unipolarity (1985-2014): Why have most countries in the region not implemented any consistent balancing or bandwagoning strategies vis-à-vis Brazil? Drawing on neoclassical realism, the article proposes that certain domestic variables - government instability, limited party-system institutionalization, and powerful presidents - have diverted the attention of political elites and foreign policy executives from the challenges generated by a rising Brazil. Crisp-set qualitative comparative analysis is used to test this hypothesis and other alternative explanations for the regional imbalance.
Keywords: 300; South America; regional powers; neoclassical realism